Three approaches to sport psychology consulting - Archer, Mark; Virtual Brands; Del Padre Visual Productions ([Wilbraham, Mass.] : Virtual Brands, 2000)
Views and compares the styles of three prominent sport psychology consultants: Burt Giges, Kenneth Ravizza, Shane Murphy
Title from title screen
Executive producers: Britt Brewer, Al Petitpas, Judy Van Raalte ; camera, Geoff Alson, Mark Archer ; editor, Nino Del Padre
Host: Al Petitpas
Consultants: Burt Giges, Kenneth Ravizza, Shane Murphy
Keywords: Sports -- Psychological aspects; Psychological consultation